Developmental defects of enamel and dentin in individuals born preterm: a scoping review of evidence and mechanisms - Sadhvi B; Manju R; Samiksha Uchil; Rupali D; Swagata Saha (Frontiers in Dental Medicine, 2026)
Background Preterm birth (<37 weeks of gestation) occurs during critical stages of odontogenesis and is associated with developmental defects in dental hard tissues. Enamel hypoplasia, enamel hypomineralization, and structural dentin alterations may compromise esthetics, function, and long-term oral health outcomes. However, the nature and extent of these defects and their underlying mechanisms have not been comprehensively investigated. Objective To map and evaluate the available evidence regarding developmental defects of enamel and dentin in individuals born preterm, identify proposed pathophysiological mechanisms, and highlight the gaps in the current literature. Methods This scoping review was conducted in accordance with the Arksey and O'Malley framework, incorporating methodological refinements proposed by Levac et al., and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR). A structured search of PubMed, Scopus, and Web of Science was performed for studies published until July 2026. Studies evaluating enamel and/or dentin outcomes in individuals born preterm (<37 weeks of gestation) were eligible for inclusion. Results Fourteen studies, including cross-sectional, cohort, case-control, longitudinal, and histological investigations, met the eligibility criteria. Enamel hypoplasia and hypomineralization were the most frequently reported defects, with greater prevalence and severity observed among individuals with lower gestational age and birth weight. Dentin alterations, including reduced mineralisation, altered hardness, and structural irregularities, were reported in only three of the included studies. Although these findings suggest an association with prematurity, the limited evidence base means that they should be regarded as preliminary and hypothesis-generating rather than conclusive. Proposed mechanisms include perinatal hypoxia, nutritional deficiencies, systemic inflammation, and neonatal intensive care–related interventions, such as endotracheal intubation and prolonged assisted ventilation. The available evidence is characterised by methodological heterogeneity, variations in diagnostic criteria, and a paucity of longitudinal studies. Conclusion Current evidence suggests that preterm birth is associated with developmental defects in both enamel and dentin. Nevertheless, significant knowledge gaps remain, particularly regarding dentin-specific pathologies, long-term outcomes, and underlying biological mechanisms. Future research should prioritise standardised diagnostic approaches and well-designed longitudinal studies to strengthen the evidence base and inform preventive and therapeutic strategies for this condition.